Fundamentalisme Islam: Gejala Ketidakmampuan dalam Merespon Makna Zaman - Moh. Shofan (Budapest International Research and Critics University, 2019)
The phenomenon of religious fundamentalism and terrorism become a very serious threat to modern society. Religiosity in the modern age is expected by the western intellectuals as 'civil religion' is far from reality. Precisely pattern that emerges is religious fundamentalism and reinforced the use of religious symbols which for fundamentalists, not only identity, but more than that, a symbol of resistance.